2020
DOI: 10.2176/nmc.oa.2019-0261
|View full text |Cite
|
Sign up to set email alerts
|

Other Hospital-onset Acute Ischemic Stroke Due to Large Vessel Occlusion Treated by Mechanical Thrombectomy after Inter-hospital Transfer

Abstract: The purpose of this study was to investigate the in-hospital acute ischemic stroke due to large vessel occlusion (LVO) that developed in another thrombectomy-incapable hospital, treated by mechanical thrombectomy after inter-hospital transfer. In eight other hospital-onset LVO patients, clinical characteristics, treatment results, and the timeline of thrombectomy were retrospectively investigated and compared to the results of 17 patients developed LVO at our own hospital and 18 developed in the community. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…1,3,18 Several studies have reported that the incidence of periprocedural complications was not significantly higher in IHOS patients compared to patients with COS, and the occurrence of sICHs was evenly distributed between the two groups. [1][2][3][4][5][18][19][20] Our meta-analysis also verified these results.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…1,3,18 Several studies have reported that the incidence of periprocedural complications was not significantly higher in IHOS patients compared to patients with COS, and the occurrence of sICHs was evenly distributed between the two groups. [1][2][3][4][5][18][19][20] Our meta-analysis also verified these results.…”
Section: Discussionsupporting
confidence: 82%
“…Several in-hospital cohorts have reported successful reperfusion grades following mechanical thrombectomy, indicating the technical feasibility of this procedure for IHOS patients [ 1 - 6 , 18 - 20 ]. Our analysis further confirmed the high rate of successful recanalization for mechanical thrombectomy in IHOS cases, which was found to be comparable to that in COS cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that thrombus retrieval therapy for in-hospital stroke with large-vessel occlusion takes longer if the patient must be transferred to another hospital. 10 In our patient, however, COVID-19 could be treated at the first hospital. Because our hospital is a single-specialty neurosurgery hospital, as mentioned previously, it was difficult to treat COVID-19; thus, after the neurosurgery, the patient returned to the general hospital where he had been hospitalized for COVID-19.…”
Section: Discussionmentioning
confidence: 61%